Respostas

2013-11-29T11:40:27-02:00
Y= x^{2}    3^{x} -10=0 => x
-(-3) + - [tex] \sqrt{ (3)^{2}-4(1)(10) }          =   3+-  \sqrt{9+40}
_________________________________________              ________________
                        2(1)                                                                   2

3+-  \sqrt{49}            =        3+-7         =>     x_{1} = 3-7   = 5
_______________________               ______                                      _____
            2                                             2                                               2

 x_{2} = 3+7    =    -2      
                          ____
                             2


{-5,2}